ANALISIS MANAJEMEN PEMASARAN BISNIS SYARIAH STRATEGI PRODUK SUPERKUE DALAM MENINGKATKAN KEPUASAN KONSUMEN (STUDI SUPERKUE TERMINAL LEUWILIANG, KABUPATEN BOGOR, JAWA BARAT) - Alviani, Siti Novia; Thantawi, Tubagus Rifqy; Fadilah, Hafid (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2024)
The purpose of this study is to analyze and explain what strategies are used by the SuperKue Shop Outlet Terminal Leuwiliang to increase customer satisfaction and to find out what factors are supporting and inhibiting in increasing customer satisfaction SuperKue Shop Outlet Terminal Leuwiliang. The data processing method consists of qualitative analysis using an inductive approach. The sample in this study is the person in charge of the outlet, the service department, the production department. The results of this study are: The results of the study show that the Leuwiliang Terminal Outlet SuperKue Store is in a sell V position, namely hold and maintain or stabilization with a total score of internal strategic factors of 2.47 and a total score of external strategy (2.42). The strategies that are usually applied to cell V are market penetration and product development. The strategy that can be applied by the SuperKuer Outlet Terminal Leuwiliang Store is that SuperKue maintains product quality and adds product variants, improves service to consumers, takes advantage of technological advances (website, Facebook, Instagram, Whatshap etc.), provides delivery services, provides discounts and prizes, opening new branches, recruiting special media employees, providing operational vehicles, maintaining various prices, providing training/comparative studies for employees, increasing the number of operational facilities and conducting promotions through print or electronic media.